Efficacy and safety of Curcuma longa extract as a treatment of primary knee osteoarthritis in adults and elderly: a systematic review - Gutiérrez Ruiz, Ana; San Mauro Martin, Ismael; Garicano Vilar, Elena; Brata, Cristian; Camina Martín, Maria Alicia (Progress in Nutrition, 2022)
Osteoarthritis (OA) is a chronic disease that leads to the wearing of joints cartilage, the most common being knee OA. The aim was to idetify the efficacy and safety of Curcuma longa extract as a potential treatment for knee OA in adults and elderly.A systematic review was conducted on different databases, using a search strategy that included curcumin, curcuma, turmeric, dietary/food/herbal supplement, phytochemical, plant extract, nutraceutical and osteoarthritis as keywords. Inclusion criteria were double-parallel randomized clinical trials in adults, diagnosed with knee OA, and published within the last 10 years. Only studies that used turmeric, not any other herbaceous substance, were included.Five studies were included. VAS, WOMAC, JKOM and KOOS scales were used. Inflammation and oxidative stress and cartilage degradation biomarkers were controlled. Statistically significant reductions in VAS, WOMAC (except stiffness) and biomarkers were observed.Curcumin may have therapeutic utility in knee OA, showing similar efficacy to conventional drug treatment, but presenting fewer adverse effects.